Intermittent Chaos in the CSTR Bray–Liebhafsky Oscillator-Specific Flow Rate Dependence - Bubanja, Itana Nuša; Ivanović-Šašić, Ana; Čupić, Željko; Anić, Slobodan; Kolar-Anić, Ljiljana (Frontiers in Chemistry, 2020)
Dynamic states with intermittent oscillations consisted of a chaotic mixture of large amplitude relaxation oscillations grouped in bursts, and between them, small-amplitude sinusoidal oscillations, or even the quiescent parts, known as gaps were experimentally generated in a Bray–Liebhafsky (BL) oscillatory reaction in an isothermal continuously-fed well-stirred tank reactor (CSTR) as a function of specific flow rate as a control parameter. They were found between two regular periodic states obtained for specific flow rate values about 0.020 min-1 and 0.082 min-1. In the terms of the largest Lyapunov exponents, calculated from experimentally obtained time series, as well as phenomenological analysis based on the quantitative characteristics of intermittent oscillations, it was shown that the chaotic complexity arises from both bifurcations approaching to the vertical asymptote which is somewhere between them showing route to fully developed chaos. Hence, the route to fully developed chaos in the Bray-Liebhafsky oscillatory reaction is proposed as an explanation for experimentally observed intermittent dynamics. This is in good correlation with our previously obtained results where the most chaotic intermittent chaos was achieved between periodic oscillatory dynamic state and stable steady state generated in BL under CSTR conditions by varying temperature and inflow potassium iodate concentration. Moreover it was shown that, besides largest Lyapunov exponent, analysis of chaos in experimentally obtained intermittent states can be achieved by simpler approach which involves usage of quantitative characteristics of the BL reaction evolution, that is the number and length of gaps and bursts obtained for various values of specific flow rates.